The Role Of Music Schools In The Emergence Of Folk Oral Creativity (Eurasian Journal of History, Geography and Economics, 2024)
Musical instruments are a means of glorifying the spirituality of humanity in battles, that is, they are the product of folk creativity, and they are miraculous and expressive instruments that have been formed among the masses for a long time, made by skilled craftsmen, and are increasingly perfected. The national pride, traditions, and values of each people are expressed in the instruments, and the sound they emit is also adapted to this. All of this serves as the basis for the form of the instruments to be created and the criterion of nationality